(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2023)
Future energy with bright prospects is renewable energy. One strategy to enhance the proportion of renewable energy in the energy mix is to switch from conventional to renewable energy-based energy sources. Previously using conventional energy sources, one of the male dormitories of Baiturrahman Boarding School will be converted to 100% renewable energy. When Homer software is used to simulate it, the best system will be chosen, with the input coming from locally available energy sources like sunlight from a photovoltaic module and biogas. From optimal output which consists of a 7.54 kW PV, a 5 kW biogas-fueled generator, an 18.78 kWh battery, and a 4 kW converter. 9.989 kW (98.13%) and a 190 kW (1.87%) biogas-fueled generator combined to produce electricity. The cost of energy is worth 0.216, and the present net cost is worth 17.769, according to the system’s economic study. The results of the sensitivity analysis show that changes in the discount rate and variations in the value of inflation have an effect on the present net cost.